2008
DOI: 10.1016/j.nbd.2007.12.003
|View full text |Cite
|
Sign up to set email alerts
|

An inverse agonist of the histamine H3 receptor improves wakefulness in narcolepsy: Studies in orexin−/− mice and patients

Abstract: Abbreviations AbstractNarcolepsy is characterized by excessive daytime sleepiness(EDS), cataplexy, direct onsets of rapid eye movement(REM) sleep from wakefulness(DREMs) and deficiency of orexins, neuropeptides that promote wakefulness largely via activation of histamine (HA) pathways. The hypothesis that the orexin defect can be circumvented by enhancing HA release was explored in narcoleptic mice and patients using tiprolisant, an inverse H3-receptor agonist. In narcoleptic orexin-/-mice, tiprolisant enhance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
179
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 249 publications
(193 citation statements)
references
References 43 publications
14
179
0
Order By: Relevance
“…Preclinical studies have shown that antagonists of the H3 receptor can induce wakefulness and that these effects are, unlike the wake promoting effects of modafinil, abolished in H3 receptor KO mice, demonstrating the very different mechanisms of actions of the two compounds (Parmentier et al 2007). In one clinical study, reduction of sleepiness in narcoleptic patients was observed after administration of a H3-inverse agonists (Lin et al 2008). In that study, however, no objective EEG data during either wakefulness or sleep were reported and it is currently not known how H3 antagonists and H3 inverse agonists affect the EEG during wakefulness and sleep.…”
Section: )mentioning
confidence: 99%
“…Preclinical studies have shown that antagonists of the H3 receptor can induce wakefulness and that these effects are, unlike the wake promoting effects of modafinil, abolished in H3 receptor KO mice, demonstrating the very different mechanisms of actions of the two compounds (Parmentier et al 2007). In one clinical study, reduction of sleepiness in narcoleptic patients was observed after administration of a H3-inverse agonists (Lin et al 2008). In that study, however, no objective EEG data during either wakefulness or sleep were reported and it is currently not known how H3 antagonists and H3 inverse agonists affect the EEG during wakefulness and sleep.…”
Section: )mentioning
confidence: 99%
“…The 6 mg once-daily dose was terminated in young adults due to increased incidence of adverse events and overall poor tolerability. The safety profile of ABT-288 appears to be consistent with other H3 receptor antagonists with typical sleep-related adverse events (insomnia, sleep disturbances, abnormal dreams) and other likely histamine-mediated adverse events (headache, nausea, sweating/hot flushes) [20][21][22][23]. Titration to improve the tolerability of higher doses was considered.…”
Section: Figurementioning
confidence: 99%
“…Indeed, acute administration of GSK189254 reduced narcoleptic episodes in orexin-knockout mice [105]. Moreover, in a pilot single-blind clinical trial on 22 patients diagnosed with narco lepsy receiving a placebo for 1 week, followed by tiprolisant (BF2.649) for a second week, the Epworth sleepiness scale (ESS) score was reduced from a baseline value of 17.6 by 1.0 with the placebo (p > 0.05), and 5.9 with tiprolisant (p < 0.001) [106]. EDS, unaffected under placebo, was nearly suppressed on the last days [108]).…”
Section: Characteristics Of the H 3 Rmentioning
confidence: 99%